Mathematical Modeling of the State of the Battery of Cargo Electric Vehicles; Mathematics; Vol. 11, iss. 3 - Martyushev N. V. Nikita Vladimirovich; Malozemov B. V. Boris Vitaljevich; Sorokova S. N. Svetlana Nikolaevna; Efremenkov (Ephremenkov) E. A. Egor Alekseevich; Tsi Mensyuy (2023, 2023)
Title screen